The embracement practice in prenatal care: limits, potentialities and contributions of nursing - Izabela Tamires Jully Pereira Gonçalves; Kleyde Ventura Souza; Marta Araújo Amaral; Aline Reis Souza de Oliveira; Walkiria Fernandes Camilo Ferreira (Rev Rene)
This study aims to analyze the practice of embracement in prenatal care, highlighting their limits and potentialities, and the contributions of nursing to its incorporation in the attention to pregnant women. This is a narrative review with search of scientific or institutional materials indexed in databases of electronic media, published from 2000 to 2010, using the subject descriptors and/or words, resulting in 32 productions. Data organization was performed, and then the content analysis, identifying four thematic categories. This study reinforced that the practice of embracement is a strategy that provides quality care during prenatal and in the relationship between the pregnant woman and the health professional. Despite the difficulties in its implementation, the practice of embracement in prenatal care may contribute to a favorable pregnancy outcome. The practice of embracement is consistent with the object of nursing care and therefore may potentiate it.